(untitled) (Philological Studies, 2019)
The article deals with the morphological category of vocative in Croatian and Serbian language norms and language use. After the core features of the category are presented, the introductory part of the article is dedicated to the display of this category in Slavic languages, with special regard to Croatian and Serbian. In the central part of the article the results of the survey on the vocative use are analyzed. The closing chapter raises two questions: (1) What are the causes and effects of losing the morphological category of vocative; (2) Should vocative be considered a case?